2007
DOI: 10.1007/s00464-007-9522-3
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic harvest of saphenous vein: a lesson learned from 1,348 cases

Abstract: The findings showed EVH of saphenous vein to be a valid alternative to open saphenectomy, providing excellent surgical results. Therefore, EVH should be considered as the standard of care for saphenous vein harvest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The literature search identified 236 studies, of which 25 met the inclusion criteria for review. Seven studies were excluded because EVH was used in combination with 24,25 or for coronary artery bypass surgery (CABG) and LEAB; 26 were commentary or review articles; 27e30 or were published as full-text, non-English articles. 31 One presentation abstract 32 was also excluded as the results were further published as a research paper.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search identified 236 studies, of which 25 met the inclusion criteria for review. Seven studies were excluded because EVH was used in combination with 24,25 or for coronary artery bypass surgery (CABG) and LEAB; 26 were commentary or review articles; 27e30 or were published as full-text, non-English articles. 31 One presentation abstract 32 was also excluded as the results were further published as a research paper.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of 1348 patients undergoing EVH revealed that the average procedural time of the first 50 cases was 68 minutes, while the procedural time dropped significantly to 23 minutes in the last 200 cases [6]. In general one can expect a personal learning curve of 20–100 procedures, depending on surgical experience.…”
Section: Procedure Learning Curve and Safetymentioning
confidence: 99%
“…The few case reports describing EVH specific complications relate to the use of CO 2 insufflation, namely, severe hypercapnia, subclinical CO 2 embolization (10.4%), and massive CO 2 embolization (0.22%) [6, 7]. An important preventive measure is reduction of the CO 2 insufflation pressure, most importantly not allowing the CO 2 pressure to surpass the central venous pressure.…”
Section: Procedure Learning Curve and Safetymentioning
confidence: 99%
“…Irrespective of the device used, a short skin incision of 2-3cm is enough to harvest the vein (two-to three-vein conduit segments and the radial artery). Several groups have reported a fast learning curve with the endoscopic technique, with procedure duration reducing to an acceptable 20-30 minutes after the first few cases 51.…”
mentioning
confidence: 99%